2017
DOI: 10.1016/j.jcma.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for recurrent pneumonia in post-irradiated patients with nasopharyngeal carcinoma

Abstract: We concluded that old age, smoking, body weight loss, and lower cranial nerve palsies are predisposing factors for multiple episodes of pneumonia in post-irradiated NPC patients. Metastatic cancer status usually leads to a lethal outcome. Early interventions to manage dysphagia in high-risk patients are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…The reason could be the high prevalence of nasogastric intubation and feeding gastrostomy rates in Taiwan 4 . Furthermore, our study that confirmed male gender, myocardial infarction, congestive heart failure, peripheral vascular disease and aneurysm, ischemic CVA, dementia, COPD, DM with or without organ damage, hemiplegia, CKD, metastatic solid tumor, and AIDS were independent predictors for AP events, consistent with the results of previous studies 5, 6, 7, 8, 9. All these systemic diseases will induce varying degrees of disability.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The reason could be the high prevalence of nasogastric intubation and feeding gastrostomy rates in Taiwan 4 . Furthermore, our study that confirmed male gender, myocardial infarction, congestive heart failure, peripheral vascular disease and aneurysm, ischemic CVA, dementia, COPD, DM with or without organ damage, hemiplegia, CKD, metastatic solid tumor, and AIDS were independent predictors for AP events, consistent with the results of previous studies 5, 6, 7, 8, 9. All these systemic diseases will induce varying degrees of disability.…”
Section: Discussionsupporting
confidence: 91%
“…An association between dysphagia and AP has been reported in clinical observations. Poor swallowing function is known to be related to aging, head and neck irradiation, myopathies, stroke, and neuromuscular disease 5 , 6 , 12, 13, 14. Dysphagia is a major healthcare problem, as it increases the risk of malnutrition, dehydration, aspiration pneumonia, and death 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Case series and cross-sectional data report alarmingly high rates of aspiration-related deaths (2123). For example, the 30-day mortality rate in a series of nasopharyngeal cancer patients was 51% (24). It is crucial that we identify those at risk of developing aspiration pneumonia as early as possible.…”
Section: Dysphagiamentioning
confidence: 99%
“…Due to increasing longevity, survivors are now suffering longer‐term side effects and complications of treatment such as dysphagia due to post‐irradiation sensory and motor neuropathies and soft tissue fibrosis 5–7 . This is an important cause of dysphagia in the south‐eastern Asian population 8–11 …”
Section: Introductionmentioning
confidence: 99%